Differentiation of Scots pine (Pinus sylvestris L.) populations in the Tatra Mountains based on needle morphological traits - Androsiuk, Piotr; Urbaniak, Lech (Biodiversity: Research and Conservation, 2006)
We investigated the variation of five needle morphological traits of the Scots pine (Pinus sylvestris L.) in four populations from the Tatra Mts. The greatest variation was found in needle length, number of stomatal rows, both on the adaxial and abaxial side of leaf, whereas the number of stomata per 2 mm of the needle length, for both sides of the leaf, showed only small intrapopulational variation. The results obtained by discriminant analysis show the distinct character of Scots pine populations from the Tatra National Park, particularly from the “Filipczańskie Skałki” locality. “Filipczańskie Skałki” is a small, isolated population differing in the number of stomata and stomatal rows.